Pimenta dioica (L.) Merr. Bioactive Constituents Exert Anti-SARS-CoV-2 and Anti-Inflammatory Activities: Molecular Docking and Dynamics, In Vitro, and In Vivo Studies - Heba A. El Gizawy; Sylvia A. Boshra; Ahmed Mostafa; Sara H. Mahmoud; Muhammad I. Ismail; Aisha A. Alsfouk; Azza T. Taher; Ahmed A. Al-Karmalawy (Molecules, 2021)
In response to the urgent need to control Coronavirus disease 19 (COVID-19), this study aims to explore potential anti-SARS-CoV-2 agents from natural sources. Moreover, cytokine immunological responses to the viral infection could lead to acute respiratory distress which is considered a critical and life-threatening complication associated with the infection. Therefore, the anti-viral and anti-inflammatory agents can be key to the management of patients with COVID-19. Four bioactive compounds, namely ferulic acid 1, rutin 2, gallic acid 3, and chlorogenic acid 4 were isolated from the leaves of Pimenta dioica (L.) Merr (ethyl acetate extract) and identified using spectroscopic evidence. Furthermore, molecular docking and dynamics simulations were performed for the isolated and identified compounds (1–4) against SARS-CoV-2 main protease (Mpro) as a proposed mechanism of action. Furthermore, all compounds were tested for their half-maximal cytotoxicity (CC50) and SARS-CoV-2 inhibitory concentrations (IC50). Additionally, lung toxicity was induced in rats by mercuric chloride and the effects of treatment with P. dioca aqueous extract, ferulic acid 1, rutin 2, gallic acid 3, and chlorogenic acid 4 were recorded through measuring TNF-α, IL-1β, IL-2, IL-10, G-CSF, and genetic expression of miRNA 21-3P and miRNA-155 levels to assess their anti-inflammatory effects essential for COVID-19 patients. Interestingly, rutin 2, gallic acid 3, and chlorogenic acid 4 showed remarkable anti-SARS-CoV-2 activities with IC50 values of 31 µg/mL, 108 μg/mL, and 360 µg/mL, respectively. Moreover, the anti-inflammatory effects were found to be better in ferulic acid 1 and rutin 2 treatments. Our results could be promising for more advanced preclinical and clinical studies especially on rutin 2 either alone or in combination with other isolates for COVID-19 management.